Systematic review and meta-analysis of positive long-term effects after intra-articular administration of orthobiologic therapeutics in horses with naturally occurring osteoarthritis - Mayet, Anna; Zablotski, Yury; Roth, Susanne Pauline; Brehm, Walter; Troillet, Antonia (Frontiers in Veterinary Science, 2023)
Equine veterinarians face challenges in treating horses with osteoarthritic joint pain in routine veterinary practice. All common treatment options aim to reduce the clinical consequences of osteoarthritis (OA) characterized by persistent synovitis and progressive degradation of articular cartilage. A range of joint-associated cell types and extracellular matrices are involved in the not yet entirely understood chronic inflammatory process. Regeneration of articular tissues to re-establish joint hemostasis is the future perspective when fundamental healing of OA is the long-term goal. The use of intra-articular applied biologic therapeutics derived from blood or mesenchymal stroma cell (MSC) sources is nowadays a well-accepted treatment option. Although this group of therapeutics is not totally consistent due to the lack of clear definitions and compositions, they all share a potential regenerative effect on articular tissues as described in in vivo and in vitro studies. However, the current stage of science in regenerative medicine needs to be supported by clinical reports as in fact, in vitro studies as well as studies using induced OA models still represent a fragment of the complex pathomechanism of naturally occurring OA. This systemic review aims to determine the long-term effect of regenerative therapeutics in horses suffering naturally occurring OA. Thereby, a meta-analysis of randomized controlled trials (RCTs) is conducted to describe the efficiency and safety of intra-articular applied regenerative therapies in terms of lameness reduction in the long-term. Using the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) guidelines, thirteen studies met the inclusion criteria for the systemic review. Four of those studies have further been evaluated by the meta-analysis comparing the long-term effect in lameness reduction. Each study was examined for risk of bias. For data evaluation, a random-effects model was used, describing the overall outcome in a forest plot. The I² statistic was used to assess heterogeneity. Results indicate, that regenerative therapeutics represent an effective long-term and safe OA treatment option. Due to the inhomogeneity of included studies, no statements are provided addressing specific regenerative joint therapies, affected joints, OA stage and horse`s intended use. Future clinical trials should follow standardized study designs to provide comparable data.